Penguatan Karakter Anak Muslim Moderat dalam Mencegah Perilaku Bullying di Sekolah - Rohmad, Muhammad Ali; Rozi, Syaikhu; Yaqin, Ainul (Proceedings of Annual Conference for Muslim Scholars, 2022)
This article is the result of a study that depicts the efforts of schools in strengthening the character of moderate Muslim children to prevent bullying behavior in schools. These efforts are relevant to government policies in encouraging the implementation of the Child Friendly School (SRA) program. The research process that produced this article was carried out qualitatively using interactive model data analysis techniques as developed by Miles and Huberman. Based on the results of the study, it can be concluded that bullying is carried out by stronger students against students who are weaker psychologically and physically when there is no teacher at school. The psychological impact of bullying is that students who are bullied feel stressed, inferior, hurt, sad, and frustrated, so they are reluctant and sometimes even afraid to go to school. The solution so that students do not do bullying is to intensively instill the character of Moderate Muslim Children in students, because among its characteristics are upholding noble character, tolerance, and not being discriminatory. The planting method is the pilot method, problem solving, and synchronic-analytic